1993
DOI: 10.1038/bjc.1993.202
|View full text |Cite
|
Sign up to set email alerts
|

A double blind placebo controlled trial of medroxyprogesterone acetate (MPA) in cancer cachexia

Abstract: Summary Patients with breast cancer treated with MPA often report an improvement in appetite. Similar appetite stimulation is seen in patients treated with some corticosteroids, but MPA has a potential advantage over these drugs in that it does not exert a catabolic effect. MPA (100 mg tds orally) has therefore been compared with placebo in 60 patients with advanced malignant disease. Twenty-one patients in the MPA group and 20 in the placebo group were receiving chemotherapy. Patients were treated for 6 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(22 citation statements)
references
References 14 publications
0
19
0
3
Order By: Relevance
“…However, the results of a recent clinical trial suggest that this adverse effect results in improvement of the anorexia and bodyweight loss induced in patients by cytotoxic agents (Tominaga et al, 1994). Moreover, MPA has been used as an anticachectic agent for patients with non-breast malignancies in a clinical trial (Downer et al, 1993). A similar clinical trial has been conducted using another synthetic progestin, megestrol acetate (Gebbia et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of a recent clinical trial suggest that this adverse effect results in improvement of the anorexia and bodyweight loss induced in patients by cytotoxic agents (Tominaga et al, 1994). Moreover, MPA has been used as an anticachectic agent for patients with non-breast malignancies in a clinical trial (Downer et al, 1993). A similar clinical trial has been conducted using another synthetic progestin, megestrol acetate (Gebbia et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported, however, that concomitant administration of MPA reduces the nausea and anorexia induced by the administration of cytotoxic agents, and subsequently reverses bodyweight loss (Tominaga et al, 1994). Based on these findings, a clinical trial using MPA as an anticachectic agent has been undertaken in patients with various malignancies which are not hormone responsive (Downer et al, 1993).…”
mentioning
confidence: 99%
“…Improvement of appetite by treatment with medroxyprogesterone acetate did not result in weight gain in patients with malignant cancer [123] and it was shown that most of the weight gain seen in that study was due to increase of adipose tissue and water [124]. The changes in metabolism and tissue catabolism in cancer patients are extensive (see [125]), but the cause leading to the metabolic changes as well as the cause of appetite suppression are poorly understood.…”
Section: "The Flesh Is Consumed and Becomes Water…the Abdomen Fills Wmentioning
confidence: 99%
“…Studies using medroxyprogesterone acetate have also been associated with a significant increase in appetite together with increases in serum thyroid binding prealbumin (transthyretin) and retinal binding protein without any concomitant changes in body weight, functional performance status, or anthropometric measurements [80,83]. On the other hand, a controlled multicenter study comparing medroxyprogesterone with a placebo demonstrated significantly approved appetite and body weight (but not quality of life) in the experimental group versus the control group in advanced-stage, non-hormone sensitive cancer [80,84].…”
Section: Progestational Agentsmentioning
confidence: 99%